Dinamika Komunikasi Politik Islam: Narasi, Dan Dampak Dalam Konteks Politik Kontemporer - Kahpi, Mhd. Latip; Siregar, Ali Syahbana; Romadhon, Sahru (IAIN Padangsidimpuan, 2024)
AbstractThis research aims to explore the dynamics of Islamic political communication, including the narratives used and their impact in the contemporary political context. Through qualitative analysis of various literary sources, mass media, and interviews with political figures and academics, this research identifies how Islamic political narratives develop and adapt in responding to challenges and opportunities in the modern era. The research results show that Islamic political communication has its own characteristics which are characterized by the use of religious symbols, moral messages and strong rhetoric to build political support and legitimacy. In addition, the impact of Islamic political communication is very diverse, ranging from increased political participation among Muslims to deeper social polarization. This research also reveals that although Islamic political communication makes a positive contribution in strengthening the identity and political awareness of the people, it also has the potential to trigger conflict if not managed wisely. In conclusion, the dynamics of Islamic political communication are very complex and play an important role in contemporary politics, demanding deeper attention in understanding their social and political implications in various contexts.Keywords: Dynamics Communication, Political Islam, Contemporary PoliticsAbstrakPenelitian ini bertujuan untuk mengeksplorasi dinamika komunikasi politik Islam, termasuk narasi yang digunakan dan dampaknya dalam konteks politik kontemporer. Melalui analisis kualitatif terhadap berbagai sumber literatur, media massa, serta wawancara dengan tokoh politik dan akademisi, penelitian ini mengidentifikasi bagaimana narasi politik Islam berkembang dan beradaptasi dalam menjawab tantangan dan peluang di era modern. Hasil penelitian menunjukkan bahwa komunikasi politik Islam memiliki ciri khas tersendiri yang ditandai oleh penggunaan simbol-simbol religius, pesan moral, dan retorika yang kuat untuk membangun dukungan politik dan legitimasi. Selain itu, dampak dari komunikasi politik Islam sangat beragam, mulai dari peningkatan partisipasi politik di kalangan umat Muslim hingga polarisasi sosial yang lebih dalam. Penelitian ini juga mengungkapkan bahwa meskipun komunikasi politik Islam berkontribusi positif dalam memperkuat identitas dan kesadaran politik umat, ia juga berpotensi memicu konflik jika tidak dikelola dengan bijaksana. Kesimpulannya, dinamika komunikasi politik Islam sangat kompleks dan memainkan peran penting dalam politik kontemporer, menuntut perhatian lebih dalam dalam memahami implikasi sosial dan politiknya di berbagai konteks.Kata Kunci: Dinamika Komunikasi, Politik Islam, Politik Kontemporer